Prediksi Harga Saham Bank BCA Menggunakan XGBoost - Beno Jange (Forum Kerjasama Pendidikan Tinggi, 2022)
This study aims to determine the prediction of Bank BCA's stock price using XGBoost. XGBoost is an open source implementation of Gradient Boosting for generating forecasts based on historical data that is fast and scalable. The data in this study is stock price data of Bank BCA for 4 (four) years, namely from 01-01-2017 to 31-12-2020. The technical indicators used in this study are the Simple Moving Average (SMA), Exponential Moving Average (EMA), Moving Average Convergence/Divergence (MACD) and Relative Strength Index (RSI). The results show that the Exponential Moving Average technical indicator greatly influences the prediction results. The results of this study also show a fairly good prediction accuracy with MAPE of 4.01 percent with hyper parameter settings; but the predictions are slightly less good in March 2020 due to the Covid-19 pandemic case.